La synthèse théologique du bien commun chez Augustin - Nebel, Mathias (Vox Patrum, 2022)
The article seeks to understand how Augustine radically reformulated the political notion of the common good of classical antiquity, from a theological perspective. The main argument is that this reinterpretation follows naturally from the New Testament theology of the koinonia uniting the Church, as shown in the letter to Volusianus and Augustine’s homilies on the Epistle to the Parthians. From this reading, it then becomes easier to understand the famous reformulation of the definition of society in books II and XIX of the City of God. We conclude by identifying the three themes that, from Augustine onwards, will be closely associated with the notion of the common good in the western political theology: 1) The common good is no longer a concept, but a Person and a Space: Christ in his humanity is the one and only Common Good of the human race. 2) The universal Common Good is eschatological; in history we can only speak of partial and imperfect common goods. 3) Charity is the driving force behind the dynamic fulfilling the universal Common Good in history.